Novel Pharmacological Inhibitors for Bacterial Protein Toxins - Holger Barth (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Many medically relevant bacteria cause severe human and animal diseases because they produce and release protein toxins that target mammalian cells. Because the toxin-induced cell damage is the reason for the clinical symptoms, the targeted pharmacological inhibition of the cytotoxic mode of action of bacterial toxins should prevent or cure the respective toxin-associated disease. Toxin inhibitors might be beneficial when the toxin acts in the absence of the producing bacteria (e.g., food poisoning), but also in combination with antibiotics in infectious diseases when the toxin-producing bacteria are present. The focus of this Special Issue of Toxins is on the development and characterization of novel inhibitors against bacterial toxins, e.g., toxin neutralizing antibodies, peptides or small compounds, as well as toxin pore blockers, which interfere with bacterial toxins and thereby protect cells from intoxication.